Wanna go Clubbing? - Senior Citizens Clubs in Kuala Lumpur eine Ethnographie von Freizeitorganisationen für ältere Menschen - Oppermann, Carolin 1982- (Kultur und soziale Praxis, 2017)
How do the elderly go clubbing? This ethnography provides new and direct insights into the organized leisure time of senior citizens